Kontrakulturele aksies op onderwysgebied - Schoeman, P. G. (Koers, 1985)
The author deals with the school criticism of the so-called "new humanism" in terms of a radical rejection of the existing norms of the Western welfare society, together with a rejection of the values and lifestyle of the "establishment". Counter-cultural criticism wishes to attain the utter destruction of existing school systems and structures.